PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN BENEISH RATIO INDEX - Agus Riyanto; Carolinna Patrichia Sulau (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
The purpose of this research is to find out the number and percentage of companies that are classified as manipulators, non-manipulators and gray companies in manufacturing companies in the consumer goods industry sub-sector on the Indonesia Stock Exchange for 2019-2021. The population of this study are manufacturing companies in the consumer goods industry sub-sector on the Indonesia Stock Exchange in 2019 to 2021, totaling 70 companies. The sample for this research was taken using a purposive sampling method with the aim of obtaining a sample that fits the criteria the researcher wanted and produced 37 sample companies. The results of the study stated that in 2019 there was 1 company (2.70%) and in 2020 no companies were found that were included in the manipulator group and in 2021 2 companies (5.41%) were found that were included in the manipulator group. In 2019 there were 33 companies (89.19%), in 2020 there were 35 companies and in 2021 35 companies (94.59%) were found to be in the non-manipulator category. In 2019 there were 3 companies (8.11%), in 2020 there were 2 companies and in 2021 there were no companies classified as gray companies.